ASPEK HUKUM AKTA NOTARIS YANG DIBUAT DILUAR WILAYAH JABATAN NOTARIS (Lex Jurnalica, 2021)
This study aims to determine and understand the legal consequences of notaries making deeds outside their respective areas of office and to determine the role of regional supervisory boards if notaries make deeds outside their respective areas of office. The research method used is normative research method. The approach method used in this research is a statutory approach method and a conceptual approach. The legal consequence is that the notary deed made outside the area of office is that the deed does not become an authentic deed and does not have legal force and becomes an underhand deed.Keywords : Notary Act, Province, Department